Tromsø som samisk by? – Språkideologier og medienes rolle i språkdebatten - Hiss, Florian (Nordlit, 2012)
This article presents a critical analysis of the discursive practices in the public debate on Sámi language in Tromsø. The conflict around the political plan of Tromsø municipality to join the administrative area for the Sámi language lasted for about one year and was largely carried out in the local newspapers, which had established themselves as an arena and broker in the conflict. The focus of this study is, on the one hand, on the role of the media in the debate and, on the other hand, on the socially constructed relations between Sámi and Norwegian language and social meanings, which get expressed in a highly ideological picture of language and local identity and form the ground for the language conflict. The analytic strategy is twofold: as a first step, the study focuses on the reproduction of language ideologies in letters to the editor and readers’ contributions to the local papers’ discussion pages. The identification of the three semiotic processes of iconization (rhematization), fractal recursivity, and erasure reveals how the writers’ expressions of opinion are anchored in a language ideology that connects Sámi language with certain social values and ignores a larger linguistic and cultural diversity in the town of Tromsø. As a second step, the analysis explores the journalistic treatment of the multitude of conflicting voices in the debate and critically sheds light on the construction of a journalistic voice. Although the journalists claim to construe a seemingly neutral ground for their reports (or independent comments), the analysis shows that journalists use the representation of various voices in their texts to construe a positioned, evaluating, and ideologically anchored journalistic voice. In face of the highly ideological character of the language debate in Tromsø, I argue that local journalism has failed in countering the ideological picture of language and society through information and independent journalism.